Bioclimatic Technology in High Rise Office Building Design: A Comparison Study for Indoor Environmental Condition - Ismail, Lokman Hakim; Sibley, Magda; Abdul Wahab, Izudinshah (Journal of Science and Technology, 2011)
The shift towards a more sustainable architecture for high-rise building is discussed and illustrated through the work of Ken Yeang and other architects. The claimed benefits of such a bioclimatic design approach are examined in the light of the results of previously conducted research projects, dealing with indoor thermal condition of high-rise office buildings. This paper reports on a study to determine if high-rise buildings designed on bioclimatic principles perform better than conventional designed ones, when situated in a tropical climate such as that in Malaysia. The paper describes a number of case studies which compare Malaysian bioclimatic and conventional building using indoor environmental parameter criteria such as air temperature, relative humidity and air velocity. Building energy index for both types of buildings is presented to illustrate the real energy savings in both types of buildings. The major finding of this work is that, the bioclimatic buildings offering a more comfortable indoor environment, increase satisfaction and show an improvement in energy saving.